Review of: “Parki i ogrody terapeutyczne” by M. Trojanowska - Gajdek, Agata (Zakład Architektury Krajobrazu, Wydział Biologiczno-Rolniczy, Uniwersytet Rzeszowski, 2018)
The problemof therapeutic properties of garden space is nowadays readily undertaken by architects, landscape architects, urban planners and gardeners. Increasing health problems that modern society is struggling with, force to search for various spatial and social solutions that enable everyday use of therapy and the beneficial influence of contact with nature. Public and urban spaces available to every inhabitant of the modern city become the natural and the most obvious area of such activities. In this context, the book “Parks and therapeutic gardensis” an interesting and valuable source of multi-faceted information and design inspirations regarding the topic discussed. The guidelines contained therein for creating new spaces and the described existing gardens indicate the possibilities of revitalization of green areas, parks and city gardens, as well as inter-block spaces.